Well-Being Interventions for Correctional Officers in a Prison Setting: A Review and Meta-Analysis - Evers, Trisha J. (Criminal justice and behavior, 2020)
This review and meta-analysis evaluated the effectiveness of well-being interventions offered to correctional officers within prison settings. A search strategy was developed and 11 databases were searched to identify eligible studies. Articles were screened against preset eligibility criteria, and quality was assessed using the Downs and Black Checklist. Nine studies were identified, including four single-group design and five quasi-experimental designed studies. Interventions comprised a mixture of crisis interventions, psychoeducational programs, and an exercise program. For those studies with sufficient data, a meta-analysis was conducted to examine intervention effects on stress and psychopathology. Fixed-effects meta-analysis showed that treatment had no effect on stress or psychopathology. Of those studies that could not be included in the meta-analysis, there were mixed outcomes. These findings highlight the need for more rigorous study designs and suggest further research is needed to examine the theoretical mechanisms in the development of interventions within correctional settings.